Assessment of nutritional support in patients after liver and kidney transplantation - Ćurić Delač, Maja (Array, 2019)
During the last decades organ transplantation has evolved into a proven therapy for end-stage organ failure. However, the long-term success of organ transplantation depends significantly on the patients’ ability to overcome possible postoperative complications and to recover from a severe metabolic imbalance. Therefore, in the present study we assessed the accuracy of the early post-operative nutritional intake in a vulnerable group of patients after organ transplantation and compared it with the calculated minimal nutritional requirements. A number of 61 patients were included in the study, 48 with liver, 11 with kidney, and two patients with both, liver and kidney transplants. Mini nutritional assessment (MNA) was applied and total nutritional intake was recorded for fourteen consecutive post-transplant days. Serum concentrations of proteins, urea and creatinine, as well as catalytic concentrations of liver enzymes were measured. Urea to creatinine ratio was calculated. According to body mass index (BMI) only a few patients were malnourished, but low serum protein levels indicated a significant protein catabolism. Nutritional requirements were provided mainly by glucose, with low amounts of proteins, i.e. amino acids, and fats. It took more than seven days to reach the appropriate nutritional intake. Because of the intensive catabolism, especially of proteins, nutrition of organ transplant recipients requires permanent monitoring and better nutritional support through formulas for enteral and total parenteral nutrition.